Calculating and reporting healthcare statistics - White, Susan; American Health Information Management Association (Chicago, Ill. : AHIMA Press, 2023)
"Calculating and Reporting Healthcare Statistics, sixth edition, is a comprehensive resource intended for healthcare professionals and students seeking to understand or sharpen their statistical computation skills. The text is organized around exercises and examples that are presented extensively using Excel calculation displays.Susan White, PhD, RHIA, CHDA,brings her expertise in the area of analyzing healthcare data to this valuable reference. Topics are updated to explore the current healthcare industry, basic math and statistical computations, vital statistics and mortality rates, census and occupancy rates, and more, all in accordance with AHIMA curriculum domains for statistics. "--Publisher information.
Includes bibliographical references and index.
Keywords: Medical statistics -- Problems, exercises, etc; Medical statistics -- Textbooks; Medical statistics; Problems and exercises; Textbooks